Utility of laboratory and immune biomarkers in predicting disease progression and mortality among patients with moderate to severe COVID-19 disease at a Philippine tertiary hospital - Punzalan, Felix Eduardo R.; Aherrera, Jaime Alfonso M.; de Paz-Silava, Sheriah Laine M.; Mondragon, Alric V.; Malundo, Anna Flor G.; Tan, Joanne Jennifer E.; Tantengco, Ourlad Alzeus G.; Quebral, Elgin Paul B.; Uy, Mary Nadine Alessandra R.; Lintao, Ryan C. V.; Dela Rosa, Jared Gabriel L.; Mercado, Maria Elizabeth P.; et al. (Frontiers in Immunology, 2023)
Purpose: This study was performed to determine the clinical biomarkers and cytokines that may be associated with disease progression and in-hospital mortality in a cohort of hospitalized patients with RT-PCR-confirmed moderate to severe COVID-19 infection from October 2020 to September 2021, during the first wave of COVID-19 pandemic before the advent of vaccination. Patients and Methods: Clinical profile was obtained from the medical records. Laboratory parameters and serum concentrations of cytokines were measured on Days 0-3, 4-10, 11-14, and beyond Day 14 from the onset of illness. Regression analysis was done to determine the association of the clinical laboratory biomarkers and cytokines with the primary outcomes of disease progression and mortality. ROC curves were generated to determine the predictive performance of the cytokines. Results: We included 400 hospitalized patients with COVID-19 infection, 69% had severe to critical COVID-19 on admission. Disease progression occurred in 139 (35%) patients, while 18% of the cohort died (73/400). High D-dimer >1 µg/mL (RR 3.5 95%CI:1.83–6.69), elevated LDH >359.5 U/L (RR 1.85 95%CI:1.05–3.25), lymphopenia (RR 1.91 95%CI:1.14–3.19), and hypoalbuminemia (RR 2.67, 95%CI:1.05–6.78) were significantly associated with disease progression. High D-dimer (RR 3.95, 95%CI:1.62–9.61) and high LDH (RR 5.43, 95%CI 2.39–12.37) were also significantly associated with increased risk of in-hospital mortality. Nonsurvivors had significantly higher IP-10 levels at 0-3, 4-10, and 11-14 days from illness onset (p<0.01), IL-6 levels at 0-3 days of illness (p=0.03) and IL-18 levels at days 11-14 of illness (p<0.001) compared to survivors. IP-10 had the best predictive performance for disease progression at days 0-3 (AUC 0.81, 95%CI:0.68–0.95), followed by IL-6 at 11-14 days of illness (AUC 0.67, 95%CI:0.61–0.73). IP-10 predicted mortality at 11-14 days of illness (AUC 0.77, 95%CI:0.70–0.84), and IL-6 beyond 14 days of illness (AUC 0.75, 95%CI:0.68–0.82). Conclusion: Elevated D-dimer, elevated LDH, lymphopenia, and hypoalbuminemia are prognostic markers of disease progression. High IP-10 and IL-6 within the 14 days of illness herald disease progression. Additionally, elevated D-dimer and LDH, high IP-10, IL-6, and IL-18 were associated with mortality. Timely utilization of these biomarkers can guide clinical monitoring and management decisions for COVID-19 patients in the Philippines.